Divine action and modern science - Saunders, Nicholas (Cambridge University Press, 2002)
Divine Action and Modern Science considers the relationship between the natural sciences and the concept of God acting in the world. Nicholas Saunders examines the Biblical motivations for asserting a continuing notion of divine action and identifies several different theological approaches to the problem. He considers their theoretical relationships with the laws of nature, indeterminism, and probabilistic causation. His book then embarks on a radical critique of current attempts to reconcile special divine action with quantum theory, chaos theory and quantum chaos. As well as considering the implications of these problems for common interpretations of divine action, Saunders also surveys and codifies the many different theological, philosophical and scientific responses to divine action. The conclusion reached is that we are still far from a satisfactory account of how God might act in a manner that is consonant with modern science despite the copious recent scholarship in this area.